POJOK MODERASI SEBAGAI PENDUKUNG PEMBELAJARAN DI ERA 4.0 - Sahid, Joko; Affandy, Fachruddin Fiqri (JRCE (Journal of Research on Community Engagement), 2024)
The aim of this research is to provide the background to the presence of the Industrial Revolution Era 4.0 where in this era the system is directed to a digital form assisted by networks. In analyzing the reading interest of students, teenagers and the entire community in the Swakarsa Luar area, West Koya, the implementation of the Moderation Corner Reading Park and Moderation Corner Study Class (TPBM and KBPM) activities based on Learning While Playing, has increased the reading interest of the Community of the Outer Swakarsa Area, West Koya . This research is included in the field research category, the type of approach used is qualitative descriptive research. This subject is focused on people who have competence, and are considered to understand TBPM and KBPM, namely founders and managers. The results of the research show that: (1) The reading interest of students, teenagers and the community of Swakarsa Luar, West Koya in visiting TBPM tends to be more influenced by external factors, so that they want to visit TBPM (2) TBPM and KBPM are not very popular among people outside of education. non-formal (3) TBPM and KBPM as one of the non-formal education programs as a learning method. (4) TBPM and KBPM are responsible for serving the community and helping non-formal students solve their learning problems at school. (5) because the research carried out is related to the impact of ship libraries; (6) The role of TBPM and KBPM is the main task that must be carried out in the Pojok Moderation Community Reading Park.